Association between serve speed and court surface in tennis - Vaverka, F.; Nykodym, J.; Hendl, J.; Zhanel, J.; Zahradnik, D. (International Journal of Performance Analysis in Sport, 2018)
The aim of the study was to determine whether the serve speed differs between Grand Slam tournaments (GSTs) played on different court surfaces. The study was carried out for both men and women (n = 70-98) who participated in four of the GSTs in 2008, 2012 and 2016 (Australian Open, French Open, Wimbledon and US Open). The following serve-speed parameters were obtained from the official GST websites: the speed of the fastest serve (FS), the average speed of the first serve in a given match (S1) and the average speed of the second serve in a given match (S2). Statistical analysis was performed using a mixed linear model procedure (NCSS 2007, Keysville, UT). FS varied irregularly, but it did not differ significantly between GSTs in the three observed years. The values of S1 and S2 for both men and women were highest in WIM in all three years, and were significantly higher than the other variables measured at the other GSTs. An association between serve speed and tennis court surface was confirmed only for S1 and S2 at fast grass court surfaces at WIM in the period 2008-2016.